ANALISIS DIMENSI KESUKSESAN IMPLEMENTASI SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) PADA SATUAN KERJA WILAYAH PROVINSI JAWA TIMUR DENGAN PENDEKATAN DELONE AND MCLEAN INFORMATION SYSTEM SUCCESS MODEL - Pambudi, Kukuh Haryu (Jurnal Ilmiah Mahasiswa FEB, 2018)
The objectives of this study are to measure how successful the implementation of Institution Financial Application System (SAKTI) is in the early piloting phase and to investigate factors that influence the success using DeLone and McLean system information success model (2003). The data of this causal-explanatory study were collected from questionnaires distributed to 61 users working in vertical offices of Directorate General of Treasury in East Java, who were selected through purposive sampling method. The results from the analysis using Partial Least Square (PLS), an alternative method of Structural Equation Modelling (SEM), show that system quality, information quality and service quality of SAKTI positively influence user satisfaction. The results also show that user satisfaction positively influences SAKTI’s net benefits.Keywords: DeLone and McLean Information System Success Model, system quality, information quality, service quality, user satisfaction, net benefit, SAKTI, partial least square (PLS)